2019
DOI: 10.3390/pharmacy7010020
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Gap between Theory and Practice; the Active Role of Inpatient Pharmacists in Therapeutic Drug Monitoring

Abstract: Many hospitals face barriers in the implementation of TDM services, this study aimed to evaluate a pharmacist-led TDM service to optimize patients’ outcomes. Adult patients who were administered vancomycin, gentamicin, or amikacin were included. The pre-phase included a retrospective assessment of patients and the intervention phase consisted of an educational program. The post-phase assessed patients based on TDM services provided by inpatient pharmacists on a 24-h, 7-day basis for 3 months. The primary outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 16 publications
2
27
2
Order By: Relevance
“…Furthermore, antimicrobial stewardship teams are widely initiated in hospitals worldwide and it has been suggested that these teams should also include a pharmacist. The pharmacist could aid in choosing the best drug formulation to use, consult on appropriate empirical and prophylactic approaches, promote switching from intravenous to oral antimicrobials, analyse drug interactions and provide information about pharmacokinetics and TDM including prescribing of the new dose based on the TDM results. Besides this, the team should be advising appropriate antimicrobial therapy taking the specific patient and condition, documenting and analysing resistance patterns into account.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, antimicrobial stewardship teams are widely initiated in hospitals worldwide and it has been suggested that these teams should also include a pharmacist. The pharmacist could aid in choosing the best drug formulation to use, consult on appropriate empirical and prophylactic approaches, promote switching from intravenous to oral antimicrobials, analyse drug interactions and provide information about pharmacokinetics and TDM including prescribing of the new dose based on the TDM results. Besides this, the team should be advising appropriate antimicrobial therapy taking the specific patient and condition, documenting and analysing resistance patterns into account.…”
Section: Discussionmentioning
confidence: 99%
“…Adequate knowledge itself does not guarantee proper practices. This situation is called as the "theory-practice gap," and many reports have suggested that practice is mainly influenced by the attitudes of HCPs [59].…”
Section: Influence Of Personal and Professional Characteristicsmentioning
confidence: 99%
“…Misinterpretation of C max due to inappropriate sample timing, in the absence of an AUC value, can result in inappropriate dosing decisions 29 . Targeted education of prescribers and pharmacists regarding TDM has been shown to enhance dose selection and ordering of appropriate TDM samples, 30 suggesting that this would be an appropriate intervention to improve amikacin use. However, obtaining specifically timed amikacin concentrations is difficult in practice.…”
Section: Discussionmentioning
confidence: 99%